Cyprinus carpio hematological changes after dietary Coffea canephora leaf extract for Aeromonas hydrophila infection - Shandy Sulistyoningrum; Gunanti Mahasri; Mohammad Faizal Ulkhaq; Hapsari Kenconojati (Depik, 2023)
Coffea canephora or robusta coffee was known as a medicinal plant that admitted various biological properties. However, its application as a medicinal plant in fish disease treatment has not been reported. This study aimed to investigate the effect of dietary robusta coffee leaf (RCL) extract on the survival rate and hematology of Cyprinus carpio infected by Aeromonas hydrophila. Two hundred fish were randomly divided into five treatment groups consisting of uninfected fish (UF), infected fish (IF), and a diet supplemented with different concentrations of RCL extract (30%, 40%, and 50%). The negative control group was injected by NaCl 0.9% and other treatment groups were injected by A. hydrophila. Feeding treatment was carried out for 7 days after clinical symptoms appeared. The results showed that RCL extract increases the survival rate and hematological parameters (number of erythrocytes, hemoglobin, and lymphocytes) significantly (P0.05). The highest survival rate (100%) was recorded in groups that accepted 50% of RCL extract. This current study indicates that RCL extract could be considered a potent medicinal plant for treating fish disease caused by A. hydrophila at the optimum dose of 50%.Keywords:AeromonasCoffea canephoraExtractHematologyCyprinus carpio